Bioremediation of the Lapindo mud contaminated soil using eco-enzyme: Case of a total petroleum hydrocarbon removal - Sulistiyaningrum, Dwi Rakhmatun; Rumhayati, Barlah; Srihardyastutie, Arie (Brawijaya University, 2026)
This research investigated the effectiveness of bioremediation of Lapindo mud-contaminated soil using an eco-enzyme for total petroleum hydrocarbons (TPH) removal. The soil samples were collected from Glagaharum and Gedang Villages, Sidoarjo, East Java, Indonesia, which have been contaminated by the Lapindo mud containing TPH. The bioremediation experiment was carried out ex situ in a container filled with contaminated soil samples, which were watered with eco-enzymes daily. Bioremediation time was optimized at 0, 7, 4, 21, and 28 days while the eco-enzymes concentration was varied at 0, 5, 10, and 15% (v/v). The concentration of TPH in the soil samples was analyzed using the gravimetric method at 0, 7, 4, 21, and 28 days. The results showed that TPH concentration was gradually decreased during remediation. The remediation removal percentage reached an optimum after 21 days. The TPH was optimally removed using the eco-enzyme at 15% (v/v), achieving 95.39%. The bioremediation of contaminated soil using eco-enzymes also increased the contents of total C and total N by 50.97% and 39.43%, respectively. However, this treatment reduces total P by 50.89%. Furthermore, the pH and temperature values for the three samples before and after the bioremediation process remained fairly stable, within the pH range of 6-7 and the temperature range of 25.7-26.2 °C.